Effects of planting time on growth, flowering and bulb production of Narcissus (Narcissus tazetta) cv. ‘Paper White’ - CHAUDHARY, DIXIT; SINGH, RANJIT; KUMAR, RAKESH (Journal of Ornamental Horticulture, 2024)
A field experiment was conducted during winter season of 2020-21 at the Research Farm of Department of Floriculture and Landscaping, Punjab Agricultural University, Ludhiana to investigate the effect of different planting dates on growth, flowering and bulb production of Narcissus tazetta cv. ’Paper white’. The bulbs were planted at five different planting dates viz., 15th September (T1), 15th October (T2), 15th November (T3), 15th December (T4) and 15th January (T5) laid out in Randomized block design with five replications. Maximum plant height (40.14 cm), highest number of sprouts per plant (33.00) and maximum width of leaves (12.19 mm) were recorded in T1. However, maximum flower size (33.56 mm) was recorded in T3. The maximum number of flowers (7.18) were recorded in T1 and minimum number of flowers (4.16) were recorded in T5. Among various bulb production parameters, maximum number of bulbs (9.30), size of bulb (43.79 mm) and weight of bulb (66.09 gm) was recorded in T1 i.e., planting of bulbs on 15th September while the minimum value of the same parameters was recorded in T5. The results of the study determined that the most suitable date for planting of Narcissus tazetta cv. ’Paper white’ is September 15th (T1) under sub-tropical conditions of Punjab.